The Appointment Of Non-Muslim Leaders: (STUDY OF SURAH AL-MÃ‚'IDAH VERSES 51 AND 57 USING SEMANTIC APPROACH) - Umum B Karyanto (Jurnal Alsinatuna, 2017)
The controversy of non-Muslim leadership in the majority of Muslims is common. Historically, this issue has been long-standing and has always invited debates among experts from time to time. In response to this issue, the Ulamas split into two camps, some forbidden, but others permitted. The Indonesian state which in fact has a majority Muslim population often experience a collision related to the appointment of non-Muslim leaders. Essentially, leadership is a mandate that must be mandated to those who can afford it. Indonesian law guarantees all its citizens to emerge as both Muslim and non-Muslim leaders. Therefore, this paper attempts to analyze the appointment of non-Muslim leaders with a semantic approach to verses of the Qur'Ã¢n that textually prohibits Muslims (believers) to appoint non-Muslims as leaders because of the words waliy and auliyÄ'which textually has the meaning of "protector and leader". The semantic approach used in this paper refers to the basic and relational meaning so that it will feel more fair in interpreting the text. Key words: non-Muslim, waliy, auliyÄâ€™, semantic, al-Qurâ€™Ã¢n.